Evaluation of Radiochemical Purity of Received 99mTc-99Mo Generator using Paper Chromatography Test - Abdallah, Yousif; Gar-elnabi, Mohamed E.; Ahmed, Siddig; Abdelmajed, Nada (Asian Journal of Medical Radiological Research, 2012)
Chromatography is a technique for separating mixtures into the components that they are made from in order to analyze, identify, quantify, or purify the mixture or components. This study was performed in Nuclear medicine Department - National Cancer Institute (NCI) University of Gazeria in period of March to May 2011. Quality control testing of the eluate from the generator was tested for the presence of molybdenum breakthrough, and radiochemical purity. These impurities was easily be detected by simple methods. The determination of Aluminum which is a non radioactive agent in the eluate needs indicator paper which could be obtained commercially. The results of chromatography were 98.48% and 98.45%, 98.44%, 98.42%, 98.40% and 98.40%. Finally the quality control of radiopharmaceuticals, if given attention in the department, will result in improving the diagnostic information, reducing the radiation doses to patients and staff, and reducing costs through effective use of radiopharmaceuticals.